Maintained complete response to talazoparib in a BRCA-2 mutated metastatic luminal breast cancer: case report and review of literature - Albarrán, Víctor; Chamorro, Jesús; Pozas, Javier; San Román, María; Rosero, Diana Isabel; Saavedra, Cristina; Gion, María; Cortés, Alfonso; Escalera, Elena; Guerra, Eva; López Miranda, Elena; Fernández Abad, María; et al. (Frontiers in Oncology, 2023)
PARP inhibitors are progressively becoming part of our therapeutic arsenal against BRCA-defective tumors, due to their capacity to induce synthetic lethality in cells with a deficiency in the homologous recombination repair system. Olaparib and talazoparib have been approved for metastatic breast cancer in carriers of germline BRCA mutations, which can be found in around 6% of patients with breast cancer. We report the case of a metastatic breast cancer patient, carrier of a germline mutation in BRCA2, with a complete response to first line treatment with talazoparib, maintained after 6 years. To our knowledge, this is the longest response reported with a PARP inhibitor in a BRCA-mutated tumor. We have made a review of literature, regarding the rationale for PARP inhibitors in carriers of BRCA mutations and their clinical relevance in the management of advanced breast cancer, as well as their emerging role in early-stage disease, alone and in combination with other systemic therapies.